2020
DOI: 10.1186/s12937-020-0525-4
|View full text |Cite
|
Sign up to set email alerts
|

Geographical influences on the iodine status in pregnant women, neonates, and school-age children in China

Abstract: Background: Pregnant women, neonates, and school-age children are vulnerable to iodine deficiency. The iodine contents in the environment (drinking water and household salt for cooking) vary by geographical location in China. The aim of this study was to assess the iodine status in vulnerable groups from different geographical zones and analyze the iodine content in household salt and drinking water from these zones. Methods: In coastal and inland regions of Zhejiang Province, China, samples of spot urine, dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…However, it should also be noted that MUIC in children was higher than 130 μg/l in all subgroups including those with PHCAIS <90% in this study ( Figure 1A ) and children who consumed non-iodized salt still had adequate iodine status ( Table 1 ). This phenomenon was also seen in the Chinese population in samples/cohorts research that was different from ours ( 10 , 20 , 21 ). Multiple possible reasons may be responsible for these observations.…”
Section: Discussionsupporting
confidence: 66%
“…However, it should also be noted that MUIC in children was higher than 130 μg/l in all subgroups including those with PHCAIS <90% in this study ( Figure 1A ) and children who consumed non-iodized salt still had adequate iodine status ( Table 1 ). This phenomenon was also seen in the Chinese population in samples/cohorts research that was different from ours ( 10 , 20 , 21 ). Multiple possible reasons may be responsible for these observations.…”
Section: Discussionsupporting
confidence: 66%
“…Since geographic in uences on the iodine status existed in pregnant and lactating women, neonates, and school-age children [26,27], and geographic locations with poor iodine status were suggested to identify [17], we then analyzed UIC differences among the three representative provinces. Our previous study concluded that the iodine nutritional status of school-age children varied among Hebei, Zhejiang and Guangxi, and lower MUIC and higher proportion of UIC < 100 µg/L was observed in Hebei and Zhejiang [9].…”
Section: Discussionmentioning
confidence: 99%
“…Though Zhejiang has achieved IDD elimination in pregnancy at a provincial level since 2011 [ 30 ], iodine status is regionally heterogeneous at a sub-provincial level, with iodine deficiency in coastal regions and iodine sufficiency in inland regions [ 27 , 31 ], presenting a unique setting throughout China to investigate the association between iodine deficiency and time required to conceive. Iodized salt accounted for 70–80% of the dietary iodine source for Zhejiang’s women [ 32 ].…”
Section: Discussionmentioning
confidence: 99%